Targeting lipid metabolism as a new therapeutic strategy for inherited cardiomyopathies - Gaar-Humphreys, Karen R.; van den Brink, Alyssa; Wekking, Mark; Asselbergs, Folkert W.; van Steenbeek, Frank G.; Harakalova, Magdalena; Pei, Jiayi (Frontiers in Cardiovascular Medicine, 2023)
Inherited cardiomyopathies caused by pathological genetic variants include multiple subtypes of heart disease. Advances in next-generation sequencing techniques have allowed for the identification of numerous genetic variants as pathological variants. However, the disease penetrance varies among mutated genes. Some can be associated with more than one disease subtype, leading to a complex genotype-phenotype relationship in inherited cardiomyopathies. Previous studies have demonstrated disrupted metabolism in inherited cardiomyopathies and the importance of metabolic adaptations in disease onset and progression. In addition, genotype- and phenotype-specific metabolic alterations, especially in lipid metabolism, have been revealed. In this mini-review, we describe the metabolic changes that are associated with dilated cardiomyopathy (DCM) and hypertrophic cardiomyopathy (HCM), which account for the largest proportion of inherited cardiomyopathies. We also summarize the affected expression of genes involved in fatty acid oxidation (FAO) in DCM and HCM, highlighting the potential of PPARA-targeting drugs as FAO modulators in treating patients with inherited cardiomyopathies.